Behave or be banned?: banning orders and selective exclusion from public space - Schuilenburg, Marc (Crime, law and social change, 2015)
By describing the practice of banning orders in the Netherlands, we investigate how the involved parties are dealing with their new responsibilities. We describe the way the changes in security management exert further influence in the spatial environment of city centers, and we analyze what this means in terms of equality of rights for all citizens. With this analysis, an attempt to explain the exercise of power beyond the State in policing space in Western countries is provided.